2023
DOI: 10.1186/s12864-023-09440-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the gut microbiota in three captive Rhinopithecus species

Abstract: Background Snub-nosed monkeys are highly endangered primates and their population continues to decline with the habitat fragmentation. Artificial feeding and breeding is an important auxiliary conservation strategy. Studies have shown that changes and imbalances in the gut microbiota often cause gastrointestinal problems in captive snub-nosed monkeys. Here, we compare the gut microbiota composition, diversity, and predicted metabolic function of three endangered species of snub-nosed monkeys (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Structural differences in gut microbiota analysis showed that in agreement with those of other rodents, such as 13-lined ground squirrels [59], arctic ground squirrels [22], and BALB/c mice [60], the gut microbiota of the wild chipmunk is mainly composed of Bacteroidetes, Firmicutes, and Proteobacteria. This is equally consistent with amphibians such as Japanese wrinkled frogs [28] Strauchbufo raddei [29] and Fejervarya limnocharis [30], and brown tree frogs [16] as well as other mammals such as snub-nosed monkeys [61] and brown bears [26]. In the hibernation group, the relative abundance of both Bacteroidetes and Firmicutes was significantly decreased, while the relative abundance of Proteobacteria was significantly increased.…”
Section: Discussionsupporting
confidence: 67%
“…Structural differences in gut microbiota analysis showed that in agreement with those of other rodents, such as 13-lined ground squirrels [59], arctic ground squirrels [22], and BALB/c mice [60], the gut microbiota of the wild chipmunk is mainly composed of Bacteroidetes, Firmicutes, and Proteobacteria. This is equally consistent with amphibians such as Japanese wrinkled frogs [28] Strauchbufo raddei [29] and Fejervarya limnocharis [30], and brown tree frogs [16] as well as other mammals such as snub-nosed monkeys [61] and brown bears [26]. In the hibernation group, the relative abundance of both Bacteroidetes and Firmicutes was significantly decreased, while the relative abundance of Proteobacteria was significantly increased.…”
Section: Discussionsupporting
confidence: 67%
“…They have also been suggested to be a marker of intestinal barrier damage ( Rao et al, 2021 ), largely due to the fact that Desulfobacterota lipopolysaccharides are severe inflammatory stimulants for the host ( Huang et al, 2021 ). Rikenellaceae_RC9_gut_group is a beneficial bacterium in the gastrointestinal tract of animals, involved in the fermentation of cellulose and capable of producing short-chain fatty acids ( Xi et al, 2023 ). Ruminococcus is a common bacterium in the feces of ruminants, mainly colonizing the jejunum and ileum of the intestinal lumen ( Guerra et al, 2022 ; Zhang et al, 2022 ), and is involved in the degradation of starch and other complex polysaccharides ( Rangarajan et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the rumen of ruminant animals, members of the Oscillospiraceae family are generally associated with cellulose degradation, as indicated in previous research [ 32 ]. Building on the understanding of other members within the family, it can be postulated that the UCG-002 genus may also play a role in the metabolism of cellulose and other complex polysaccharides within the rumen environment [ 33 , 34 ]. As such, Oscillospiraceae_UCG-002 could provide the host with essential nutrients, particularly SCFAs such as propionate or butyrate, which are crucial sources of energy for ruminant animals.…”
Section: Discussionmentioning
confidence: 99%